Evaluation of Several Genes as Targets for RNAi in German Cockroach - Banister, Hayley; Zhu, Kun Yan; Silver, Kristopher (My University, 2017)
RNA interference (RNAi) was first discovered in nematodes when exogenous double-stranded RNA (dsRNA) complementary to a specific gene suppressed expression of that gene [1]. Subsequently, much effort has been devoted to developing RNAi as a highly specific tool for therapeutic interventions and control of insect pests [2]. However, there are still many challenges associated with using RNAi to control insects, including efficient delivery and selection of appropriate targets. In this study, we evaluated three genes as potential targets for causing mortality via RNAi in German cockroach, Blatella germanica. German cockroaches are ubiquitous structural pests that can serve as reservoirs for species of pathogenic bacteria, viruses, or fungi in humans [3,4] and is an excellent organism for exploring insect control using RNAi. Injection of dsRNA complementary to either tubulin (Tub, a cytoskeletal structural protein), VATPase subunit 1 (Vha, an integral membrane protein), or Snf7 (an ESCRT III protein) caused decreased survival with Snf7 causing the greatest and fastest mortality (LT50 = 8.2 days). Our results demonstrate that when suppressed with RNAi, these genes could be effective targets for cockroach control. Furthermore, knowing these genes can be effectively used for RNAi, we can now attempt to understand why methods other than injection for RNAi delivery are less efficient in an effort to improve the utility of RNAi in insect control.
Citation: Banister, H. (2017). Evaluation of Several Genes as Targets for RNAi in German Cockroach . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.